Temperature affects major fatty acid biosynthesis in noug (Guizotia abyssinica) self-compatible lines - Gebeyehu, Adane; Hammenhag, Cecilia; Tesfaye, Kassahun; Ortiz, Rodomiro; Geleta, Mulatu (Frontiers in Nutrition, 2024)
Noug (Guizotia abyssinica) is an economically important edible oilseed crop in Ethiopia with a large variation in seed set, seed oil content, and fatty acid composition among populations. Although noug is generally strictly self-incompatible (SI), self-compatible (SC) lines were recently developed. This study was conducted to investigate the levels of variation in seed setting and oleic acid content among the self-compatible lines. The starting materials for the seed setting study were 200 genotypes selected from 100 inbred lines and having, on average, 57 seeds per capitulum, which is higher than that of the SI populations. The SC genotypes were analyzed for their oleic acid content using the half-seed technique. The analysis of 20 SC lines revealed a high variation in oleic acid content with 70% of the SC lines having 20% or more oleic acid after they were grown under 25oC/21oC day/night temperatures (high-temperature treatment). The oleic acid content increased from 8.2% before to 22.5%, on average, after the high-temperature experiment in the greenhouse. In contrast, the percentage of oleic acid in these lines grown at 21°C/18°C day/night temperatures decreased from 8.2% to 4.4% on average. There was a highly significant positive correlation between oleic acid content and temperature in SC lines. The study also suggests a significant contribution of genotype to the variation in seed setting and environmental factors (mostly temperature) to the oleic acid content. Overall, the noug SC lines showed highly significant variation in seed setting and oleic acid content, which could be used for improving the crop's seed yield and oil quality.